Decanuclear Ln10 Wheels and Vertex‐Shared Spirocyclic Ln5 Cores: Synthesis, Structure, SMM Behavior, and MCE Properties1. Issue 47 (30th September 2015) - Das, Sourav; Dey, Atanu; Kundu, Subrata; Biswas, Sourav; Narayanan, Ramakirushnan Suriya; Titos‐Padilla, Silvia; Lorusso, Giulia; Evangelisti, Marco; Colacio, Enrique; Chandrasekhar, Vadapalli
Abstract: The reaction of a Schiff base ligand (LH3 ) with lanthanide salts, pivalic acid and triethylamine in 1:1:1:3 and 4:5:8:20 stoichiometric ratios results in the formation of decanuclear Ln10 (Ln=Dy(1 ), Tb(2 ), and Gd (3 )) and pentanuclear Ln5 complexes (Ln=Gd (4 ), Tb (5 ), and Dy (6 )), respectively. The formation of Ln10 and Ln5 complexes are fully governed by the stoichiometry of the reagents used. Detailed magnetic studies on these complexes (1 –6 ) have been carried out. Complex1 shows a SMM behavior with an effective energy barrier for the reversal of the magnetization ( U eff )=16.12(8) K and relaxation time ( τ o )=3.3×10 −5  s under 4000 Oe direct current (dc) field. Complex6 shows the frequency dependent maxima in the out‐of‐phase signal under zero dc field, without achieving maxima above 2 K. Complexes3 and4 show a large magnetocaloric effect with the following characteristic values: −Δ S m =26.6 J kg −1  K −1 at T =2.2 K for3 and −Δ S m =27.1 J kg −1  K −1 at T =2.4 K for4, both for an applied field change of 7 T. Abstract : Homometallic complexes : The reaction of a multidentate flexible Schiff base ligand (LH3 ; see figure) with [LnCl3 ]⋅ 6 H2 O affords homometallic decanuclear complexes, [Ln10 (LH)10 (κ 2 ‐Piv)10 ] (Ln=Dy, Tb, and Gd), and homometallic pentanuclear complexes, [Ln5 (LH)4 (μ2 ‐η 1 η 1 Piv)4 (η 1 Piv)(S)] (Ln=Dy, Tb, and Gd). The Dy 3+ analogues exhibit single‐molecule magnet (SMM) behavior, whereas the Gd 3+ complexes show a significant magnetocaloric effect (MCE).